Step 1: Rewrite the equation
-4x + 7 = 2y - 3
Step 2: Given that you already have possible solutions, substitute them in for x and y
A) -4(2) + 7 = 2(1) - 3
-8 + 7 = 2 - 3
-1 = -1
B) -4(5) + 7 = 2(-5) -3
-20 + 7 = -10 -3
-13 = -13
Step 3 (final step): When looking at these two solutions, you see that both A and B work, as the result is equal on both sides. This would make the final answer:
C) Both (2,1) and (5,-5)
With the explanation above as shown work
Hope this helps comment below for more questions :)